Securities Crowdfunding (SCF) Syariah Berbasis Sukuk Sebagai Solusi Permodalan UMK Halal Di Indonesia - Syamsuri, Syamsyuri; Jakiyudin, Ahmad Havid; Wicaksono, Muhamad Budi (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2023)
The significant role of halal Micro and Small Enterprises (MSEs) in Indonesia's economy and the challenges they face in accessing capital from conventional financial institutions. With the rise of digital financial technologies, Sharia-based Securities Crowdfunding (SCF) platforms using sukuk offer a promising alternative for providing halal-compliant funding to these enterprises, facilitating their growth and contribution to the halal industry. Therefore, The purpose of this research is to evaluate the feasibility of using Sharia-based Securities Crowdfunding (SCF) with sukuk as an alternative financing solution for halal Micro and Small Enterprises (MSEs) in Indonesia. The proposed method utilizes a prospective analysis to determine the viability of a sukuk-based Sharia SCF using qualitative descriptive research methods, including literature studies, are employed to delve more into the findings of the analysis. The study's findings indicate that sukuk-based Sharia SCF can serve as a viable alternative source of business capital that is assured to be halal. MSE actors have the opportunity to enhance their business by leveraging the SCF provider platform in Indonesia, which offers attractive investment returns. SHAFIQ and LBS Crowdfunding are platforms that facilitate the execution of sharia-compliant investments, specifically sukuk. Enforcing halal certification as a requirement can serve as a catalyst for the growth of the Micro, Small, and Medium Enterprises (MSE) sector in Indonesia, positioning it as a key player in the halal industry by 2024. The research implies that sukuk-based Sharia Securities Crowdfunding (SCF) can significantly improve capital access for halal Micro and Small Enterprises (MSEs) in Indonesia, fostering their growth and sustainability. This approach also strengthens Indonesia's position in the global halal market by ensuring halal compliance in financing.